The Influence of Price and Promotion on Purchase Decisions at Manja Space Cafe, Sintang Regency - Yudi Pandra; Yasir Hudzaifah; Joko Susilo (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to analyze the influence of price and promotion on consumer purchase decisions at Manja Space Cafe, Sintang Regency. The sample consisted of 100 respondents selected through purposive sampling specifically, consumers above 18 years of age who make independent purchase decisions. The findings indicate that both price and promotion have a significant effect, either partially or simultaneously, on purchase decisions. The R² value of 80.7% indicates that promotion exerts a more dominant influence than price. These findings affirm the critical importance of implementing appropriate promotional and pricing strategies in driving consumer purchase decisions.